Coordination européenne des politiques économiques - Aglietta, Michel; de Boissieu, Christian; Bureau, Dominique; Gauron, André; Herzog, Philippe; Jacquet, Pierre; Muet, Pierre-Alain (Paris : La Documentation française, 1998)
Bibliotheek François Vercammen
Frans
Monografie